1991
DOI: 10.1080/10408399109527558
|View full text |Cite
|
Sign up to set email alerts
|

The effects of postharvest treatment and chemical interactions on the bioavailability of ascorbic acid, thiamin, vitamin a, carotenoids, and minerals

Abstract: All recent health recommendations include admonitions to reduce calories, maintain desirable weight, reduce fat, increase complex carbohydrates, and ensure an adequate intake of nutrients. Such recommendations require that we know not only nutrient composition of foods, but also potential losses and decreased bioavailability due to postharvest treatment and chemical interactions. This article discusses in some detail the reactions of concern that cause such changes and their potential alleviation with several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
7

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 150 publications
2
29
0
7
Order By: Relevance
“…A number of dehydration procedures are employed for fruits and vegetables, i.e., sun-, cross flow-, drum-, spray-, puff-, freeze-and microwavedrying (Chong and Law 2010). For most vegetables, drying resulted in 10-20 % loss of carotenoids (Clydesdale et al 1991), with the increased surface area of dried or powdered products leading to further losses (through autoxidation) unless they were protected from air and light. Specially, dehydration (heating) cause significant quantitative changes in carotenoid isomers, which was also observed in present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…A number of dehydration procedures are employed for fruits and vegetables, i.e., sun-, cross flow-, drum-, spray-, puff-, freeze-and microwavedrying (Chong and Law 2010). For most vegetables, drying resulted in 10-20 % loss of carotenoids (Clydesdale et al 1991), with the increased surface area of dried or powdered products leading to further losses (through autoxidation) unless they were protected from air and light. Specially, dehydration (heating) cause significant quantitative changes in carotenoid isomers, which was also observed in present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of chemical interactions on thiamin stability in complex food systems has been reviewed (Clydesdale et al, 1991). The major form of thiamin in meat products is protein-bound thiamin pyrophosphate (TPP).…”
Section: Stabilitymentioning
confidence: 99%
“…bCarotene content is reported to increase during storage (Brown, 1949;Clydesdale et al, 1991;Lee, 1986;Rygg, 1949), and some of the samples obtained in February for this study were storage samples. Hochmuth et al (1999) reported that b-carotene concentrations are influenced by nitrogenous fertilizers.…”
Section: Carotene Contentmentioning
confidence: 98%